Power supply interference in smart sensor microcontroller interface - Tijani, Ismaila; Khan, Sheroz (IIUM Press, 2011)
Signal conditioning circuits otherwise referred to as sensor interface play important roles in data acquisition systems especially with microcontroller based systems. They are employed for signals conversion or translations to squeeze the acquired signal into a desirable range easily acceptable for the microcontroller. Many interfaces (signal conditioning circuits) have been proposed in the recent times in this regards, [1-3]; for instance, it is been employed to convert the measurand into a periodic modulated output signal which can be directly process by the microcontroller without needing an extrinsic AID converter [3]. In [1], relaxation oscillator based conditioning circuit was proposed for proper transmission of sensor output to microcontroller